Pengaruh Sumber Dana Eksternal dan Internal Perusahaan Terhadap Rentabilitas Modal Sendiri - Wiwiek Kusumaning Asmoro; Novie Astuti Setianingsih; Eti Putranti (Politeknik Ganesha Medan, 2023)
The purpose of this study was to determine the effect of the company's external and internal sources of funds on the Profitability of Own Capital (RMS) in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2018-2020. The variables used consist of the dependent variable, namely Rentability of Own Capital (RMS) and independent variables from external funds consisting of Debt to Total Capitalazition Ratio (DCR), Total Debt to Total Assets (DAR) and Debt to Equity (DER). Meanwhile, internal funding sources consist of Flow Back Ratio (FBR). The sampling technique used purposive sampling, namely the sampling technique with certain considerations. The number of samples in this study were 75 manufacturing companies with an observation period of 2018-2020. The results of this study indicate that 4 (four) independent variables consisting of DCR, DAR,DER as an external source of funds and Flowback Ratio as an internal source of funds simultaneously affect to RMS. The conclusion from the results of the study is that companies must be able to increase capital in order to increase the value of the company in order to compete to gain and increase investor confidence. Company management needs to adjust the composition of the use of FBR as internal capital by optimizing the management of assets owned.